The comparison of three dimensional and two dimensional evaluation of varus/valgus stress X-rays following total knee arthroplasty - Hiroki Hijikata; Tomoharu Mochizuki; Keisuku Maeda; Osamu Tanifuji; Go Omori; Noriaki Yamamoto; Hiroyuki Kawashima (Journal of Orthopaedic Surgery and Research)
Abstract Purpose The purpose of this study was to compare three-dimensional (3D) and two-dimensional (2D) evaluation of the stress X-rays following total knee arthroplasty (TKA). Methods This prospective study analyzed 51 consecutive rTKAs (four males and 44 females, both aged 74 ± 6 years). Postoperative varus/valgus stress X-rays were taken at maximum manual varus/valgus stress during knee extension under anesthesia, and were analyzed three-dimensionally using a 3D-2D image matching technique with 3D bone and component models. The 3D models of the femur and tibia, along with component-bone constructs, were reconstructed from CT data using 3D modeling software. The 2D evaluation of varus/valgus stress X-rays were carried out directly on the stress X-rays. The varus/valgus angle (VV angle) between components, Medial joint opening (MJO) and lateral joint opening (LJO) were assessed under conditions of no stress, valgus stress, and varus stress. Results The VV angles under no stress, valgus stress, and varus stress in 3D and 2D evaluation were 3.6 ± 1.1 / 3.6 ± 1.1°, -0.6 ± 1.6 / -0.6 ± 1.6°, 7.1 ± 1.9 / 6.8 ± 2.5°, respectively. The MJO in the non-stress condition and under valgus stress in 3D and 2D evaluation were 0.0 ± 0.5 / -1.8 ± 0.8 mm,1.4 ± 1.0 / -0.2 ± 1.4 mm, and the LJO in the non-stress condition and under varus stress in 3D and 2D evaluation were 0.9 ± 1.0 / -0.6 ± 1.0 mm, 3.5 ± 1.9 / 2.1 ± 1.9 mm, respectively. Conclusions This prospective study revealed that the 3D evaluation of varus/valgus stress X-rays following total knee arthroplasty is equivalent to 2D evaluation in VV angles, whereas different from 2Devaluation in MJO and LJO.